Indices of Increased Decompression Stress Following Long-Term Bed Rest - Gennser, Mikael; Blogg, S. L.; Eiken, Ola; Mekjavic, Igor B. (Frontiers in Physiology, 2018)
Human extravehicular activity (EVA) is essential to space exploration and involves risk of decompression sickness (DCS). On Earth the effect of microgravity on physiological systems is simulated in an experimental model where subjects are confined to a 6° head-down bed rest (HDBR). This model was used to investigate various resting and exercise regimen on the formation of venous gas emboli (VGE), an indicator of decompression stress, post hyperbaric exposure. Eight healthy male subjects participating in a bed rest regimen also took part in this study, which incorporated five different hyperbaric exposure (HE) interventions made before, during and after the HDBR. Interventions i – iv were all made with the subjects lying in 6° HD position. They included i) resting control, ii) knee-bend exercise immediately prior to HE, iii) HE during the 5th week of the 35-day HDBR period, iv) supine cycling exercise during the HE. In intervention (v), subjects remained upright and ambulatory. The HE protocol followed the Royal Navy Table 11 with 100 min spent at 18 m (280 kPa), with decompression stops at 6 m for 5 min, and at 3 m for 15 min. Post-HE, regular precordial Doppler audio measurements were made to evaluate any venous gas emboli produced post-dive. VGE were graded according to the Kisman Masurel scale. The number of bubbles produced was low in comparison to previous studies using this profile (Kisman Integrated Severity Score (KISS) ranging from 0 – 1,), and may be because subjects were young, and lay supine during both the HE and the 2 h measurement period post-HE for interventions i – iv. However, the HE during the end of HDBR produced significantly higher maximum bubble grades and KISS score than the supine control conditions (p < 0.01). In contrast to the protective effect of pre-dive exercise on bubble production, a prolonged period of bed rest prior to a hyperbaric exposure appears to promote the formation of post decompression VGE. This is in contrast to the absence of DCS observed during EVA.